ANALISIS YURIDIS TERHADAP GUGATAN MASYARAKAT ATAS TANAH PEMERINTAH KABUPATEN POLEWALI MANDAR YANG TELAH MEMILIKI SERTIFIKAT (STUDY KASUS PUTUSAN NO.40/PDT.G/2021/PN. POL) - Rahayu, Ade; Latief, Abdul (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2022)
In human life, land is one of the objects that is widely disputed, because every year it has an increasing selling value, so that humans will try to own and control it and even the land of others who already have certificates wants to be owned and controlled. Community lawsuit over the land of Takatidung Village Office where the Polewali Mandar District Government has a certificate for control of the land. In this case, it is necessary to have public legal awareness so as not to necessarily file a lawsuit for an object without a valid authentic evidence. This study aims to analyze community lawsuits over certified land and find out its legal force and use qualitative descriptive research methods.Based on the results of this study, the Local Government of Polewali Mandar Regency has strong Juridical Evidence before the law because it has a basis of Rights in the form of a Right of Use Certificate (SHP) Number 21 of 2006 for the object of dispute claimed by the community. A certificate is proof of rights issued by the National Land Agency (BPN) to the rightful owner of a land or building so that the owner gets certainty and legal protection. In this case, the Panel of Judges of the Polewali District Court proved by analyzing the contents of the plaintiff's suit and the defendant's disclaimer, adjusted to the written evidence and testimony of witnesses so as to produce legal facts. The Polewali Mandar District Government as the defendant was declared to be the rightful owner of the object of dispute.